2015
DOI: 10.1007/s10973-015-4973-6
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic zinc ferrite reduction by means of mixtures containing hydrogen and carbon monoxide

Abstract: Solid waste generation is one of the main problems in the steelmaking process. One of the most problematic waste products is the electric arc furnace dust, which is a by-product rich in iron and zinc and is present as zincite (zinc oxide) or franklinite (zinc ferrite). This work focuses on the reduction kinetics of synthetic zinc ferrite by gases containing hydrogen and carbon monoxide. This process was examined via forced stepwise isothermal analysis. The test was conducted at temperatures ranging from 500 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…This is also consistent with the peak broadening and splitting in the PXRD patterns of the corresponding samples, since small changes in lattice parameters are expected for different degree of calcium substitution of the manganese sites in MnO. EDS analysis did not show any presence of zinc in the catalysts, indicating that any zinc species formed during the reaction are reduced and sublimated during the reaction [35,36]. Ultra-small nanoparticles covering the surface of MnO are also observed, which correspond to metallic cobalt, as confirmed by EDS analysis.…”
Section: Reverse Water Gas Shift Catalytic Experiments Using Multimet...supporting
confidence: 84%
“…This is also consistent with the peak broadening and splitting in the PXRD patterns of the corresponding samples, since small changes in lattice parameters are expected for different degree of calcium substitution of the manganese sites in MnO. EDS analysis did not show any presence of zinc in the catalysts, indicating that any zinc species formed during the reaction are reduced and sublimated during the reaction [35,36]. Ultra-small nanoparticles covering the surface of MnO are also observed, which correspond to metallic cobalt, as confirmed by EDS analysis.…”
Section: Reverse Water Gas Shift Catalytic Experiments Using Multimet...supporting
confidence: 84%
“…In general, the reduction and the recovery of zinc increase with the rising temperatures. The results indicated that the temperature of 750 °C was insufficient for the volatilization of zinc [26,27]. Increasing the temperature to 850 °C resulted in increased the zinc removal rate from 22.11 to 63.39%.…”
Section: Microwave Processing Of Eaf Dustmentioning
confidence: 98%
“…It was also observed iron peaks, which suggests reduction of wustite to iron. Meanwhile, it has been reported [16] for temperatures higher than 800°C zinc oxide is also reduced to metallic gaseous zinc, which indicates zinc oxide reduction in this step. Figure 5c shows peaks of zinc oxide, wustite and iron in the third stage (850-950°C), which indicates that both zinc oxide and wustite are still being reduced at this stage.…”
Section: Reduction Of Eafd Pelletsmentioning
confidence: 99%
“…3 [13][14][15]. In a previous paper [16], it was studied the reduction of synthetic zinc ferrite pellets by CO and H 2 mixture. It was noted that synthetic zinc ferrite was reduced to zinc oxide (ZnO) and iron oxide (Fe 3 O 4 ) at temperatures lower than 550°C.…”
Section: Introductionmentioning
confidence: 99%